Constructed Language and Cultural Identity: A Sociolinguistic Analysis of Fremen Language in “Dune (2021)” Movie - Nurul Hilma Salimah; Otong Setiawan Djuharie (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
adapted movie from a novel by Frank Herbert, with the same title. The movie follows a story of Paul Atreides, who went to a desert planet named Arrakis. This study explores how language shapes group identity by examining how the Fremen language is used in “Dune (2021)”. Through some selected scenes, the research employs a qualitative approach, by examining character interactions, socio-political dynamics, and the symbolic significance of the Fremen language in shaping cultural identity. The findings show that the Fremen language not only contributes to the film's cultural representation's authenticity but also reflects  wider themes of adaptation, resistance, and the relationship between language and power. This study contributes to the discourse about constructed languages in media by highlighting how they enhance cultural identity and providing insights on the sociolinguistic implications of constructed languages in modern movies.